Micronutrient powder distribution through Maternal, Neonatal and Child Health Weeks in Nigeria: process evaluation of feasibility and use. Issue 10 (15th September 2015) - Korenromp, Eline L; Adeosun, Opeyemi; Adegoke, Femi; Akerele, Adekunle; Anger, Catherine; Ohajinwa, Chimere; Hotz, Christine; Umunna, Larry; Aminu, Francis
Abstract: Objective: To determine the feasibility of distributing micronutrient powders (MNP) for home fortification during biannual Maternal, Neonatal and Child Health Week (MNCHW) events, as a strategy to improve young child nutrition. Design: We evaluated the coverage, delivery, use and adherence of MNP, and associated behaviour change communication (BCC) materials and social mobilization, through cross-sectional surveys of caregivers attending health-service distribution events and health workers involved in MNP distribution, facility-based observations of MNP distribution activities and a repeated survey of caregivers in their homes who received MNP for their child. Setting: Four Local Government Areas in Benue State, Nigeria. Subjects: Caregivers of children 6–59 months of age attending health-service distribution events. Results: The 8 million MNP delivered in this pilot during three distribution events were estimated to reach about one-third of eligible children in the area at each event. Programme fidelity was limited by shortages of MNP, BCC materials and inadequate social mobilization, with some limitations in health worker training and engagement. MNP use was consistent with the recommended two or three sachets per week among 51–69 % of caregivers surveyed at home. Conclusions: MNP coverage was low, but consistent with that typically achieved with other services delivered through MNCHW in Benue. Among caregivers who received MNP, acceptance and use among targeted children was high. While some weaknesses in knowledge and delivery of MNP by health workers were observed, health system strengthening and more extensive social mobilization would be key to achieving higher coverage with MNP and other health services provided through MNCHW.